“Precision,” “Perfection,” and the Reality of British Scientific Instruments on the Move During the 18th Century - Baker, Alexi (Material Culture Review, 2012)
Early modern British “scientific” instruments, including precision timekeepers, are often represented as static, pristine, and self-contained in 18th-century depictions and in many modern museum displays. In reality, they were almost constantly in physical flux. Movement and changing and challenging environmental conditions frequently impaired their usage and maintenance, especially at sea and on expeditions of “science” and exploration. As a result, individuals’ experiences with mending and adapting instruments greatly defined the culture of technology and its use as well as later efforts at standardization.